Optically dressed three-level coherence in neutral bosonic alkaline-earth-like species - P. Robert; D. O. Sabulsky (Physical Review Research)
Addressing the optical clock transition of alkaline-earth-like atoms has garnered increasing interest in the context of a future redefinition of the Système International second, as well as for fundamental physics based on inertial sensors. To be accessible in bosonic alkaline-earth-like atoms, this transition necessitates external coupling. Here we propose a scheme utilizing midinfrared to deep-infrared optical dressing to drive a three-level coherence that mixes into and therefore addresses the optical clock transition of bosonic alkaline-earth-like atoms.